Basis for health care reform - Gusso, Gustavo Diniz Ferreira (2015)
The reforms in the health systems of Western European countries and Canada in the second half of the twentieth century inspired the movement known as Health Reform in Brazil. These countries have implemented socialized health systems integrating public funding and private services, some originated from universal health insurance (Bismarckian) and others from general tax revenues (Beveridgean). In this process, one of the factors that has evolved is the contracting that enables identification of fraud and promotes health at the individual and collective level rather than indiscriminate use of services. In Brazil, the 1988 Constitution lays the foundation for a universal health care system funded by general taxes while allowing the expansion of private services without state regulation, but co-financed by the state through tax exemption and subsidies for public employees. In this scenario, dichotomy increases, and the overlap between state and private services is aggravated.